2012
DOI: 10.1109/tcbb.2011.138
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Approaches for Retrieving Protein Tertiary Structures

Abstract: The 3D conformation of a protein in the space is the main factor which determines its function in living organisms. Due to the huge amount of newly discovered proteins, there is a need for fast and accurate computational methods for retrieving protein structures. Their purpose is to speed up the process of understanding the structure-to-function relationship which is crucial in the development of new drugs. There are many algorithms addressing the problem of protein structure retrieval. In this paper, we prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Zhou, Chou, & Wong, 2006). Some noteworthy global approaches include the work in (Mirceva et al, 2012) where wavelet-based protein descriptors are proposed, the work in (Sael et al, 2008) where the 3D geometrical surface of the protein structures are represented by 3D Zernike descriptors, and the approaches proposed in (Harder et al, 2012) where Gauss integral vectors are extracted from protein structures represented as open curves.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou, Chou, & Wong, 2006). Some noteworthy global approaches include the work in (Mirceva et al, 2012) where wavelet-based protein descriptors are proposed, the work in (Sael et al, 2008) where the 3D geometrical surface of the protein structures are represented by 3D Zernike descriptors, and the approaches proposed in (Harder et al, 2012) where Gauss integral vectors are extracted from protein structures represented as open curves.…”
Section: Introductionmentioning
confidence: 99%
“…Some limitations of distance matrix are its sensitivity to the parameters and its high dimensionality. Wavelets were proposed to reduce the distance matrix dimensionality [60] and extract features [61]. Marsolo and Ramamohanarao [60] reduce the dimensionality of protein structure by generating a feature vector of approximation coefficients by applying 2-dimensional wavelet decomposition of the distance matrix which allows fast retrieval of similar structures.…”
Section: A Global-structure Comparison-based Approachmentioning
confidence: 99%
“…An average accuracy of 87% was achieved at SCOP superfamily level using a k-d tree and a 10-nearest-neighbor on a dataset consists of 33,000 proteins. Recently, Mirceva et al [61] performed different wavelet transforms on the protein distance matrix and found that Daubechies2 wavelet gives the highest retrieval accuracy of 91.3%.…”
Section: A Global-structure Comparison-based Approachmentioning
confidence: 99%
“…Over the last couple of years, there have been several publications that have promoted fast algorithms for database-wide comparisons [1,8,9,10] (see the related work in [11,12,13,14,15,16,17,18,19]). These algorithms are designed to efficiently discern if two proteins share a similar molecular structure.…”
Section: Introductionmentioning
confidence: 99%